Leila Ahmed’s A Border Passage (2012) and Nawal Saadawi’s A Doctor’s Memoir (2012) as a Model of Creative Nonfiction - Walid Abdallah (IJCAS (International Journal of Creative and Arts Studies), 2023)
Memoir is a creative literary device of recording memories that can generate narrative immersion because of their aesthetic and literary techniques. Memoirs are written in a figurative language tackling real life experience, they are also a form of creative nonfiction which represents a real-life event in a literary style. This study focuses on memoirs as a form of nonfiction recently gaining more interest among writers and expanding in publication arena. Moreover, it aims at illustrating two important aspects: how creative nonfiction has the same narrative and dramatic effect as fiction, though it differs from it, and how Leila Ahmed’s A Border Passage (1999) and Nawal Saadawi’s A Doctor’s Memoir (2012) employ literary techniques in their memoirs to convey their messages in a compelling creative style. The two works are tackled from a postcolonial ecocritical perspective which illustrates the far-reaching effect of both colonization and environment on the shaping of the two writers’ awareness and ideology.A Border Passage karya Leila Ahmed (2012) dan Memoar Seorang Dokter Karya Nawal Saadawi (2012) Sebagai Model Nonfiksi Kreatif Abstrak Memoar adalah perangkat sastra kreatif untuk merekam kenangan yang dapat menghasilkan narasi yang mendalam karena teknik estetika dan sastranya. Memoar ditulis dalam bahasa kiasan yang membahas pengalaman kehidupan nyata, juga merupakan bentuk nonfiksi kreatif yang merepresentasikan peristiwa kehidupan nyata dalam gaya sastra. Kajian ini berfokus pada memoar sebagai salah satu bentuk nonfiksi yang akhir-akhir ini semakin banyak diminati oleh para penulis dan semakin meluas dalam kancah publikasi. Selain itu, artikel ini bertujuan untuk mengilustrasikan dua aspek penting: bagaimana nonfiksi kreatif memiliki narasi dan efek dramatis yang sama dengan fiksi, meskipun berbeda dari fiksi, dan bagaimana A Border Passage (1999) karya Leila Ahmed dan A Doctor's Memoir (2012) karya Nawal Saadawi menggunakan karya sastra. teknik dalam memoar mereka untuk menyampaikan pesan mereka dalam gaya kreatif yang menarik. Kedua karya ini diambil dari perspektif ekokritik pascakolonial yang menggambarkan dampak luas kolonisasi dan lingkungan terhadap pembentukan kesadaran dan ideologi kedua penulis.